GM crops: a safe link in the food supply chain? Has the science behind the EU law on GM crops failed to address the relevant risks and harms that cultivation and consumption of such crops pose to the environment and human health? - Nagodkins, Andrejs (Riga Graduate School of Law, 2018)
The purpose of this paper is to make an analysis on whether the existing EU legislation sufficiently covers all aspects related to cultivation and consumption of genetically modified crops, and, if not, to propose possible enhancements of the latter. The author concluded that the risks, identified by the author, in general terms are properly addressed in the EU, except for the issue of chelating qualities of certain chemical substances in plant protection products, e.g., glyphosate which can bind to certain metallic minerals in soils thus making such elements unavailable for plants for the proper functioning of their biological processes. And therefore, this quality of glyphosate-based herbicides should be studied in more detail, preferably in conditions that, as far as possible, would represent the actual trends of glyphosate-based herbicide use among farmers in the European Union; that is, the studies should concentrate on assessing the actual effects of entire herbicide formulation, even combinations thereof as used by farmers, instead of focusing on studying a separate active ingredient.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Genetically modified crops